Does physiotherapy reduce the incidence of postoperative pulmonary complications following pulmonary resection via open thoracotomy? A randomised single-blind clinical trial - Reeve, JC; Nicol, K; Stiller, K; McPherson, KM; Birch, P; Gordon, IR; Denehy, L (AUT University, 2010)
Postoperative pulmonary complications are an important cause of morbidity following thoracotomy and physiotherapy interventions are commonly provided with the aim of preventing and treating these. This study aimed to determine if prophylactic postoperative respiratory physiotherapy reduced the incidence of postoperative pulmonary complications and decreased length of stay in patients following pulmonary resection via thoracotomy. Seventy six patients undergoing elective thoracotomy were randomised to a treatment group (n = 42) receiving respiratory physiotherapy interventions on a daily basis until discharge or a control group (n = 34) who received standard care involving a clinical pathway but no postoperative physiotherapy intervention. Postoperative pulmonary complication data were recorded daily throughout hospitalisation by a physiotherapist blinded to group allocation using a diagnostic tool previously described. There was no significant difference between groups in baseline demographic data or in surgical interventions. Overall incidence of postoperative pulmonary complications was 3.9% (n = 3) and there was no significant difference between the incidence of postoperative pulmonary complications in the Treatment and Control Group (p = 1.00, absolute risk reduction -0.02, 95% CI -0.13 to 0.11). No significant difference was found between groups for LOS (p = 0.87), with the median (interquartile range) length of stay for the Treatment Group 6.0 (4.0) and the Control Group 6.0 (1.0) days. Given the low incidence of postoperative pulmonary complications, these results suggest that prophylactic postoperative respiratory physiotherapy may not be required in addition to standard care involving a clinical pathway following open pulmonary resection.